The Politicization of Bureaucracy in General Elections - Al Faruq, Abdurahman; Kholid Alfirdaus, Laila; Kushandajani (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2025)
This study examines the bureaucratic politicization of the State Civil Apparatus (Aparatur Sipil Negara/ASN) in the 2024 Boyolali Regency Legislative Election. Using a qualitative case study approach, it explores the forms of politicization, the dynamics of patron-client relationships, and their effects on local democracy. Data were collected through in-depth interviews with active and retired ASN personnel, expert informants, along with document reviews and field observations. The findings show that bureaucratic politicization occurs through political directives in official ASN forums, the requirement to submit Family Cards (KK) as vote reports, the withdrawal of ASN funds for party victories, and pressure exerted through career mutation and career obstacles. The main discovery is a new pattern of clientelism, where ASN are used as political actors, often replaced by volunteers or civil brokers. Therefore, this research advances the clientelism literature (Hicken, 2011; Berenschot, 2018) by emphasizing that the bureaucracy is not only an object of politicization but also a tool for systematic political patronage.